LEGAL STATUS OF AUTHENTIC DEED CONFIDENTIALITY DRAFTED BEFORE NOTARY WITH SWORN TRANSLATORS - Cahyadi, Gede Dwiki; Sukandia, I Nyoman; Renaya, Nengah (jfpublisher, 2024)
In Indonesia, authentic legal deeds must be written in Bahasa Indonesia as required by law. Notaries are responsible for maintaining the confidentiality of these documents according to the Notary Position Act and the Code of Ethics. When parties involved are not proficient in Bahasa Indonesia, a sworn translator is required to ensure the deed's authenticity and validity. The notary must oversee the accurate translation or explanation of the deed's contents, especially if they are unfamiliar with the language in which the deed is written. This research aims to examine and analyze the vagueness of legal norms regarding whether the confidentiality status of authentic deeds is still classified as confidential in the presence of a sworn translator in the deed drafting according to the Notary Position Act as well as the responsibilities of sworn translators regarding their participation for the sake of constitutional law. This research applies normative and literature review method with statutory and legal concept approach. The research findings indicate that the confidentiality of an authentic deed prepared by a notary with the assistance of a sworn translator is legally protected. Both the notary and the translator are bound by law to maintain the deed's confidentiality, with specific legal provisions requiring them to adhere to their professional ethics. Sworn translators are responsible for ensuring accurate translations and may face civil or criminal liability for breaches of confidentiality or inaccuracies in their work. This includes potential penalties under the Civil Code and Criminal Code for unlawful acts or false testimony.